Brief Report: Relationship Among Viral Load Outcomes in HIV Treatment Interruption Trials. (1st July 2016) - Treasure, Graham C.; Aga, Evgenia; Bosch, Ronald J.; Mellors, John W.; Kuritzkes, Daniel R.; Para, Michael; Gandhi, Rajesh T.; Li, Jonathan Z.
Abstract : Abstract: Viral load (VL) rebound timing and set point were analyzed in 235 participants undergoing analytic treatment interruption (ATI) in 6 AIDS Clinical Trials Group studies. There was no significant association between rebound timing and ATI VL set point for those who rebounded ⩽12 weeks. VL set points were lower in participants with rebound >12 weeks ( P < 0.001) and participants treated during early infection ( P < 0.001). Pre-antiretroviral therapy VL correlated with set point, though 68% of participants had a set point lower than pre-antiretroviral therapy VL. These results illustrate complex relationships between post-ATI virologic outcomes and the potential presence of biological factors mediating rebound timing and set point. Abstract : Supplemental Digital Content is Available in the Text.